Two-beam interference lattice lightsheet for structured illumination microscopy. (18th November 2019) - Chang, Bo-Jui; Tang, Wei-Chun; Liu, Yen-Ting; Tsai, Yun-Chi; Tsao, Chieh; Chen, Peilin; Chen, Bi-Chang
Abstract: Combining super-resolution structured illumination microscopy (SIM) and lattice lightsheet microscopes (LLSMs) has always been an ideal approach for high spatiotemporal resolution in 3D applications. We propose a simpler method to perform 2D-SIM with three phases, which is 5/3 faster and less sensitive to optical alignment compared to 3D-SIM in LLSM. In this research, we modify the original square lattice lightsheet to become an ideal pattern for the 2D-SIM by filtering the illumination pattern on the back pupil of the excitation objective. We show that the generated lattice pattern is consistent in the experiment and the simulation. We achieved a spatial resolution of 184  ±  28 nm, 244  ±  48 nm and 384  ±  20 nm in the x, y   and z directions, respectively for 2D-SIM in LLSM, with an exposure time of 5 ms for each phase per plane. For biological applications, we perform 2D-SIM in LLSM by imaging the dynamics of actin and membrane ruffling in a U2OS cell, with an exposure time of 20 ms per phase and two colors recorded for 121 optical-sectioning planes per 3D stack.